2020
DOI: 10.1038/s41419-020-03073-w
|View full text |Cite
|
Sign up to set email alerts
|

Proline-rich transmembrane protein 2 (PRRT2) regulates the actin cytoskeleton during synaptogenesis

Abstract: Mutations in proline-rich transmembrane protein 2 (PRRT2) have been recently identified as the leading cause of a clinically heterogeneous group of neurological disorders sharing a paroxysmal nature, including paroxysmal kinesigenic dyskinesia and benign familial infantile seizures. To date, studies aimed at understanding its physiological functions in neurons have mainly focused on its ability to regulate neurotransmitter release and neuronal excitability. Here, we show that PRRT2 expression in non-neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…These results, along with the evidence that homozygous mutations can cause in humans developmental delay, intellectual disability, and brain structural alterations, strongly support an additional role of PRRT2 in neurodevelopment. Indeed, one recent study has showed that in primary hippocampal neurons, PRRT2 silencing affects synaptic actin dynamics, leading to defects in dendritic spine density and maturation, through the defective interaction with cofilin, an actin-binding protein that is abundantly expressed at the synaptic level ( 54 ). Interestingly, the expression of a cofilin phospho-mimetic mutant was able to rescue PRRT2 -dependent defects in synapse density, spine number, and morphology, but not the alterations observed in neurotransmitter release ( 54 ), which confirms an independent mechanism arguably underpinning the neurodevelopmental phenotype.…”
Section: Pathophysiologic Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, along with the evidence that homozygous mutations can cause in humans developmental delay, intellectual disability, and brain structural alterations, strongly support an additional role of PRRT2 in neurodevelopment. Indeed, one recent study has showed that in primary hippocampal neurons, PRRT2 silencing affects synaptic actin dynamics, leading to defects in dendritic spine density and maturation, through the defective interaction with cofilin, an actin-binding protein that is abundantly expressed at the synaptic level ( 54 ). Interestingly, the expression of a cofilin phospho-mimetic mutant was able to rescue PRRT2 -dependent defects in synapse density, spine number, and morphology, but not the alterations observed in neurotransmitter release ( 54 ), which confirms an independent mechanism arguably underpinning the neurodevelopmental phenotype.…”
Section: Pathophysiologic Aspectsmentioning
confidence: 99%
“…Indeed, one recent study has showed that in primary hippocampal neurons, PRRT2 silencing affects synaptic actin dynamics, leading to defects in dendritic spine density and maturation, through the defective interaction with cofilin, an actin-binding protein that is abundantly expressed at the synaptic level ( 54 ). Interestingly, the expression of a cofilin phospho-mimetic mutant was able to rescue PRRT2 -dependent defects in synapse density, spine number, and morphology, but not the alterations observed in neurotransmitter release ( 54 ), which confirms an independent mechanism arguably underpinning the neurodevelopmental phenotype. The observed plateauing of PRRT2 expression during adulthood further supports the existence of critical age windows for the occurrence of related phenotypes ( Figure 1 ) and their self-limiting character ( 5 , 28 ).…”
Section: Pathophysiologic Aspectsmentioning
confidence: 99%
“…PRRT2 modulates intrinsic neuronal excitability by interacting with α-subunit of Na V 1.2/1.6 channels 9 . In addition, it plays a role in neurotransmitter release and synaptic plasticity by interacting with the SNARE complex and the Ca 2+ sensors synaptotagmin1/2 proteins 2 , 8 , 35 , and regulates synapse and spine formation by modulating actin dynamics 36 . Moreover, more than one proteomic study identified PRRT2 as a potential AMPA receptor auxiliary protein 37 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The α3 and α1 NKA-superecliptic pHluorin (SEP) constructs were generated by Dr. Anita Aperia 22 : SEP is inserted in the NKA extracellular loop between transmembrane domains 3 and 4, flanked with flexible linkers to minimize structural interference. PRRT2 silencing (SH1 and SH4) and control (scramble) shRNA sequences inserted into a pLKO.1-CMV-bicistronic lentiviral vector carrying a Tourquoise reporter have been previously generated and characterized 8 , 36 . For rescue experiments an Sh-resistant version of mouse PRRT2 fused to the mCherry reporter and inserted in the p743.pCCLsin.PTT.hPGK.GFP.Wpre_mut_AMP lentiviral vector and a Cherry variant control have been previously characterized 8 , 9 .…”
Section: Methodsmentioning
confidence: 99%
“…In mature neurons PRRT2 is enriched at synapses, where it participates to the regulation of neurotransmitter release by interacting with proteins of the synaptic vesicle fusion machinery [6]. Recently, we described a structural role for PRRT2, involving a link with the dynamic changes in the actin cytoskeleton which occur during the process of synaptogenesis [7]. These findings raise the possibility that PRRT2 plays a role also in the early stages of neuronal development, in which actin dynamics play a critical role.…”
Section: Introductionmentioning
confidence: 90%